Maritime Studies in the Wake of the Byzantine Shipwreck at Yassiada, Turkey - Carlson, Deborah N., 1970-; Kampbell, Sarah M., 1980-; Leidwanger, Justin (Book collections on Project MUSE., 2015)
In 2007 a symposium was held at Texas A & M University to celebrate the twenty-fifth anniversary of Texas A & M University Press's publication of the first volume reporting the Yassiada shipwreck site. Seventeen papers from that symposium featured in this book broadly illustrate such varied topics as ships and seafaring life, maritime trade, naval texts, commercial cargoes, and recent developments in the analysis of the Yassiada ship itself.